Aspects of Superplasticity of Metals - Tipalin, Sergey A.; Ryabov, Vladimir A.; Kalpin, Yili G. (Diffusion and defect data. Solid state data. Pt. A, Defect and diffusion forum, 2021)
The assumption that stable deformation depends on the strain rate is verified. In case of stable deformation, local deformation in a weak cross-section leads to hardening of the metal. Its effect exceeds the effect of reducing the cross-sectional area, as a result of which the deformation affects other sections as well, while the deforming force increases. At low strain rates that are characteristic of superplasticity, the strain inside the grains cannot be really great. During hot deformation, there is resistance to intragrain deformation, intergrain sliding, and accommodation of grain boundaries. The phenomenon of superplasticity is investigated and fixed under stable and unstable deformation, which leads to contradictory results. It is shown numerically that the function of deformation resistance and stable deformation rate increases only when the deformation is carried out with acceleration. The effect of hardening of the surface layer of metal grains on the deformation parameters is described.